Serum Levels of MicroRNA-371a-3p (M371) Can Predict Absence or Presence of Vital Disease in Residual Masses After Chemotherapy of Metastatic Seminoma - Dieckmann, Klaus-Peter; Klemke, Markus; Grobelny, Francesca; Radtke, Arlo; Dralle-Filiz, Inken; Wülfing, Christian; Belge, Gazanfer (Frontiers in Oncology, 2022)
Background Radiological evaluation of postchemotherapy residual masses of metastatic seminoma is characterized by poor diagnostic accuracy. Serum levels of microRNA-371a-3p (M371) involve high specificity and sensitivity for the primary diagnosis of seminoma. We evaluated if M371 levels can indicate the presence of vital disease in postchemotherapy residual masses in patients with metastatic seminoma. Methods Twenty-three seminoma patients (median age 52 years) with residual masses had posttreatment measurements of serum M371 levels (group A), fourteen of whom had measurements also beforehand. The posttreatment results were compared with the clinical outcome during follow-up. Eleven patients with complete remission after treatment of metastatic seminoma (group B) and 33 males with non-malignant testicular diseases (group C) served as controls. M371 serum levels were measured by quantitative real time PCR using miR-30b-5p as endogenous control. Evaluation was performed with descriptive statistical methods. Results Twenty-two patients of Group A had uneventful follow-up so far, twenty-one of whom had M371 levels < 5, one other had a mildly elevated level below RQ = 10. One patient with a level of RQ = 26.2 rapidly progressed. The median posttreatment M371 level of the non-progressing patients of group A is not significantly different from the median level of the control group with complete remission (B). Before treatment, the median M371 levels in groups A and B were 507.6 and 143.9, respectively. In both groups, significant drops of M371 levels resulted from treatment. Conclusion Normal M371 serum levels at the time of completion of treatment of metastatic seminoma indicate the absence of vital seminoma in residual masses while elevated levels > RQ = 10 predict the presence of disease. Optimal timing of M371 measurement after chemotherapy and the appropriate cut-off level still need to be determined. Based on the present results, measuring serum M371 levels involves the potential of a novel tool for assessing postchemotherapy residual masses of metastatic seminoma.